Design case of the E-19 AEOLUS supersonic business jet - Smith, Howard; Sun, Yicheng (American Institute of Aeronautics and Astronautics (AIAA), 2020)
This paper introduces the E-19 AEOLUS supersonic business jet designed by the authors (conceptual design) and a team of Staff and a team of graduate students (preliminary and detail design) from the Aerospace Vehicle Design MSc. The design is presented at the 50th anniversary of the first flight of Concorde and with growing interest from many aircraft design companies. An attractive design would still need the usual attributes of safety, security, comfort, reliability, performance and operational flexibility. This paper presents a design that attempts to address these issues. The details of cabin, structures, landing gear, systems, powerplants, etc. are designed. Low-boom low-drag technologies are applied to the design. The synthetic vision display and double drooping nose are introduced to increase the pilot’s field of view. The resulting concept is challenging but could result in an aircraft well suited to meet a new market opportunity
Keywords: Aircraft design